Swiss goods exports and the Sino-US trade war: Conflicting transmission mechanisms - Simon J. Evenett (Aussenwirtschaft, 2019)
This paper identifies various channels through which the Sino-US trade war and the January 2020 truce affect Swiss goods exports. As a third party to this bilateral trade war, Switzerland's goods exports were not targeted directly. Nevertheless, Swiss goods exports were implicated and evidence is presented that scales different transmission mechanisms. Given that leading central banks eased monetary policy partly on account of the macroeconomic consequences of the Sino- US trade war, a new dimension to the trade and monetary nexus has arisen. The consequences of this for the conduct of Swiss monetary policy are discussed.
Keywords: F13; F52; 330; trade war; trade diversion; protectionism; tariffs; China; United States